Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.ypmed.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring obesity and smoking among U.S. women of reproductive age: Associations with educational attainment and health biomarkers and outcomes

Abstract: Introduction Obesity and smoking are independently associated with socioeconomic disadvantage and adverse health effects in women of reproductive age and their children, but little is known about co-occurring obesity and smoking. The purpose of this study was to investigate relationships between co-occurring obesity and smoking, socioeconomic status, and health biomarkers and outcomes in a nationally representative sample. Methods Data from non-pregnant women of reproductive age were obtained from the U.S. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…13 We have recently characterized the co-occurrence of smoking and obesity among disadvantaged women and their significant association with adverse health biomarkers in a nationally representative sample. 14 We have also shown that among women who quit smoking during pregnancy, breastfeeding rates are lower in obese compared to normal weight women, suggesting that maternal BMI moderates the effects of smoking cessation on breastfeeding. 15 In this study, we sought to examine possible moderating effects of maternal BMI on associations of smoking cessation on short-term perinatal outcomes.…”
Section: Introductionmentioning
confidence: 66%
“…13 We have recently characterized the co-occurrence of smoking and obesity among disadvantaged women and their significant association with adverse health biomarkers in a nationally representative sample. 14 We have also shown that among women who quit smoking during pregnancy, breastfeeding rates are lower in obese compared to normal weight women, suggesting that maternal BMI moderates the effects of smoking cessation on breastfeeding. 15 In this study, we sought to examine possible moderating effects of maternal BMI on associations of smoking cessation on short-term perinatal outcomes.…”
Section: Introductionmentioning
confidence: 66%
“…This may limit the generality of the observations to younger age women and adolescents. Second, generality to women with less than a high school education may be limited as they were underrepresented in this sample compared to nationally representative samples (e.g., Vurbic et al, 2015). Finally, this study used a relatively new online data collection platform and a somewhat more educated sample, which has the potential to introduce reporting or sample biases such as the somewhat higher prevalence rates of e-cigarette use mentioned above (Nayak, Pechacek, Weaver, & Eriksen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking during pregnancy is the leading preventable cause of poor pregnancy outcomes in the US and other developed countries (Bonnie, Stratton, & Wallace, 2007; Cnattingius, 2004; Pauly & Slotkin, 2008). The adverse consequences of smoking during pregnancy or raising children in a smoking environment have led researchers to target women of reproductive age as an important population to study in understanding risk from use of tobacco and nicotine delivery products (e.g., Ahluwalia, Mack, & Mokdad, 2004; Hand, Heil, Sigmon, & Higgins, 2015; Vurbic et al, 2015). …”
mentioning
confidence: 99%
“…This problem too is coming to be overrepresented among more socioeconomically disadvantaged populations, especially women (Vurbic et al, 2015–in this issue). …”
Section: Behavior Change Health and Health Disparitiesmentioning
confidence: 99%
“…Further driving home the need to be mindful of co-morbid conditions and risk factors, Vurbic et al (2015–in this issue) report an original study on the prevalence of co-morbid obesity and cigarette smoking in a nationally representative sample of U.S. women of reproductive age. Each of those conditions alone is overrepresented in socioeconomically disadvantaged women, and a risk factor for pregnancy complications, poor birth outcomes, and other poor health biomarkers and outcomes.…”
Section: Physical Inactivity Obesity Cigarette Smoking and Other Tobamentioning
confidence: 99%